Analisis Dinamika Makro Ekonomi Indonesia Terhadap Return on Assets Pada Bank Umum Devisa Dengan Loan to Deposit Ratio Sebagai Variabel Intervening Pasca Krisis Ekonomi Global - Kenji Destiara (Sekolah Pascasarjana Perbanas Jakarta, 2021)
This study aims to analyze the influence of Indonesia's macroeconomic dynamics on return on assets in foreign exchange commercial banks with loan to deposit ratio as an intervening variable after the global economic crisis. The sample used in this study was 20 foreign exchange public banks listed on the Indonesia Stock Exchange with the period 2008-2017 the sample technique used in this study used a purposive sampling method. This research uses panel data regression method and the estimation model used is the Random Effect Model with a significance level of 5% of this study using Eviews 8.0 software in data processing.The results of this study indicate that: 1. inflation has a negative and not significant effect on Return to Asset Ratio (ROA), 2. interest rates have a positive and significant effect on Return to Asset Ratio (ROA), 3. the exchange rate has a positive and significant effect on Return to Asset Ratio (ROA), 4 Gross Domestic Product (GDP) has a positive and significant effect on Return to Asset Ratio (ROA), 5. Inflation has a positive and insignificant effect on the Loan to Deposit Ratio (LDR), 6. Interest rates have a positive and significant effect on the Loan to Deposit Ratio (LDR), 7. the exchange rate has a negative and significant effect on the Loan to Deposit Ratio (LDR), 8. Gross Domestic Product (GDP) has a positive and significant effect on the Loan to Deposit Ratio (LDR), 9. Loan to Deposit Ratio (LDR) ) positive and not significant effect on Return to Asset Ratio (ROA), 10. inflation has an effect on Return to Asset Ratio (ROA) does not require the role of LDR as an intervening factor, 11. interest rates affect ROA does not require the role of LDR as an intervening factor, 12. the exchange rate influences ROA requires the role of LDR as an intervening factor, 13. Gross Domestic Product has an effect on ROA requiring the role of the LDR as an intervening factor.